Soil Structure Interaction of a Mid Rise Building frame for Seismic Load Considering Soft & Loamy Soil Condition using Analysis Tool SAP2000 - Tiwari, Niket Kumar; Patel, Rakesh; Tiwari, Gaurav (International Journal of Scientific Research in Civil Engineering, 2019)
Now a day the human life and the environment have frequently been endangered by the natural hazards like earthquake, tsunami, flood, cyclone and landslides. As a consequence of which the human society and the nation’s economy get hampered immediately after the occurrence of a natural disaster. In developing countries like India, where the population is very large and is increasing day by day, the social and economic factors force the people to live in vulnerable areas, due to which the effects of these natural disasters are catastrophic. Among all these threats, liquefaction of soil can be pointed out as one of the most disastrous seismic hazards. Hence evaluation of liquefaction susceptibility is an important aspect of geotechnical engineering. soil-structure interaction effect in the analysis and design of RC frame buildings is increasingly recognized but still not penetrated to the grass root level owing to various complexities involved. It is well established fact that the soil-structure interaction effect considerably influence the design of multi-storey buildings subjected to lateral seismic loads. In this study we are performing seismic assessment using Analytical tool SAP2000 over a mid rise building frame where we will provide lateral load for zone V (0.36) to determine soil structure interaction for lateral loads, for this study a mid rise symmetrical building of G+7 storey is considered.
Keywords: Soil Interaction; Analysis Tool; Mid Rise Building; Support Reaction; Forces